2018
DOI: 10.1186/s12970-018-0216-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine intake on muscle strength and power: a systematic review and meta-analysis

Abstract: Background: Caffeine is commonly used as an ergogenic aid. Literature about the effects of caffeine ingestion on muscle strength and power is equivocal. The aim of this systematic review and meta-analysis was to summarize results from individual studies on the effects of caffeine intake on muscle strength and power. Methods: A search through eight databases was performed to find studies on the effects of caffeine on: (i) maximal muscle strength measured using 1 repetition maximum tests; and (ii) muscle power a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
227
6
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 239 publications
(304 citation statements)
references
References 39 publications
28
227
6
4
Order By: Relevance
“…Caffeine ingestion resulted in increased vertical jump height in the CMJ. The ES magnitude of 0.15 observed in this study is very similar to the pooled ES of 0.17 reported in a recent meta-analysis of 10 studies [36]. This result, therefore, confirms that caffeine ingestion may have a relatively small performance-enhancing effect on vertical jump height [36][37][38].…”
Section: Effects Of Caffeine On Exercise Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…Caffeine ingestion resulted in increased vertical jump height in the CMJ. The ES magnitude of 0.15 observed in this study is very similar to the pooled ES of 0.17 reported in a recent meta-analysis of 10 studies [36]. This result, therefore, confirms that caffeine ingestion may have a relatively small performance-enhancing effect on vertical jump height [36][37][38].…”
Section: Effects Of Caffeine On Exercise Performancesupporting
confidence: 90%
“…The ES magnitude of 0.15 observed in this study is very similar to the pooled ES of 0.17 reported in a recent meta-analysis of 10 studies [36]. This result, therefore, confirms that caffeine ingestion may have a relatively small performance-enhancing effect on vertical jump height [36][37][38]. The acute improvement in vertical jump height following caffeine ingestion is comparable to the improvement in jump height found as a result of 4 weeks of plyometric training [39,40].…”
Section: Effects Of Caffeine On Exercise Performancesupporting
confidence: 89%
“…In response to the high demands for isometric strength and resistance that sailors must face [11,12], as well as the high % VO 2max they reach as the speed increases [9,14], those athletes who consume caffeine (20% sailors of international level and 25% of those of national level) can benefit from the use of this supplement. Since the molecular form resembles that of adenosine, caffeine blocks adenosine receptors, activating the central nervous system, which decreases the subjective perception of effort, while enhancing glycolytic metabolism, neuromuscular recruitment, and the bioavailability of calcium in myoplasm [52]; moreover, previous studies have demonstrated its ergogenic effect on the improvement of muscle strength [53] and in the face of high-intensity efforts [54].…”
Section: Discussionmentioning
confidence: 99%
“…These 11 items refer to specification of eligibility criteria (item 1), study randomization (item 2), concealed allocation (item 3), similarity of groups at baseline (item 4), blinding (items 5, 6, and 7), number of participants that completed the trials (item 8), intention to treat (item 9), reporting of results (item 10), and reporting of variability in the results (item 11). Based on the summary score, the studies were classified as: (a) excellent quality (9-10 points); (b) good quality (6-8 points); (c) fair quality (4-5 points); or (d) poor quality (less than 3 points), as done in previous reviews [13][14][15]). Two authors (the first and second author) performed the appraisal of methodological quality independently.…”
Section: Methodological Qualitymentioning
confidence: 99%